Quizizz as Distance Learning Tool: Effects and Students' Opinion - Tanalina Hasnata Saniata Azta Ramadani; Lulu Salma Fajria; Sarah Fitria (JournEEL, 2021)
The purposes of this study are: (1) To determine the effect of using Quizizz as a distance learning tool, and (2) To determine students' opinions of Quizizz as a distance learning tool. The participants of this study consisted of an English teacher and thirty-one eleventh-grade students. The data used in this study are in the form of interview results, description of students’ final grades, and the result of questionnaire. The method used is a mixed-method – qualitative and quantitative, with three instruments: Likert Scale questionnaire, interview, and students’ final score. The main findings of this study are: (1) Positive effects in increasing students’ learning motivation, competitiveness, and academic achievement in grammar and reading when using Quizizz as a distance learning tool, and (2) Students’ positive opinions towards Quizizz’s interesting appearance, challenging features, and their enjoy feelings while using Quizizz as distance learning tool.